1999
DOI: 10.1508/cytologia.64.441
|View full text |Cite
|
Sign up to set email alerts
|

Karyological Studies on Some Taxa of the Genus Vicia L. (Fabaceae).

Abstract: Summary Karyological studies on 16 species of Vicia L., including 10 species from the Egyptian flora are presented. Chromosome counts are observed for two species for the first time (2n=10 in V cinerea and V nigra). A diploid number of 2n=10 (x=5) has been found in 4 species, 2n=12 (x=6) in 2 species and 2n=14 (x=7) was recorded in 10 species V hirsuta was found to have 2 B-chromosomes. The karyotype in the examined species is more or less symmetric. However, considerable variations exist in chromosome size am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Present report for Vicia faba 2n=12 tallies with the perusal of literature (Langer & Koul, 1982;Rost, 1982;Tanaka & Ohta, 1982;Anis et al, 1998 ;Zhang, 1998;Kamel, 1999;Koul et al, 1999).The reports n=6 by Kesavacharyulu et al (1982) and Jahan et al (1994) have indicated that this taxa is with the basic number x=6. The irregular number n=4, 5, 6, 7 reported by Wang & Zheng (1985) maybe due to disploidy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Present report for Vicia faba 2n=12 tallies with the perusal of literature (Langer & Koul, 1982;Rost, 1982;Tanaka & Ohta, 1982;Anis et al, 1998 ;Zhang, 1998;Kamel, 1999;Koul et al, 1999).The reports n=6 by Kesavacharyulu et al (1982) and Jahan et al (1994) have indicated that this taxa is with the basic number x=6. The irregular number n=4, 5, 6, 7 reported by Wang & Zheng (1985) maybe due to disploidy.…”
Section: Discussionsupporting
confidence: 80%
“…V. faba L. 2n=12 Langer & Koul (1982), Rost (1982), Tanaka & Ohta (1982), Zhang et al (1982), Langer & Koul (1984), Zhang (1986), Yuan (1986), Yeh et al (1986), Sato (1988), Li (1989), Chen (1989), Rizzoni et al (1989), Matsuda & Muramatsu (1989), Schubert & Rieger (1990), Hizume (1992Hizume ( , 1993, Unnikrishna Pillai & Verma (1992), Schifi no-Wittmann et al (1994, Bisht et al (1998), Anis et al (1998), Zhang (1998), Kamel (1999), Koul et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…These small chromosomes appeared to be similar to Bchromosomes. Recently, Kamel (1999), performed karyological studies on 16 species of Vicia L. Among the findings reported include the presence of two Bchromosomes in Vicia hirsuta. The presence of Bchromosomes is reported to exist in Vicia (Kamel, 1999) and further investigation is necessary to definitively determine the presence of such phenomena in V. pannonica.…”
Section: Resultsmentioning
confidence: 99%
“…Zarco (1986) has proposed the two indices A 1 and A 2 for karyotype asymmetry based on these changes. In Asteraceae growing in Egypt, detailed karyotype features for 23 species of subfamily Asteroideae were described by Badr et al (1997) and karyotypes of additional 36 species of Asteraceae were described by Kamel (1999; and Badr et al (2009). Shams (2004) confirmed counts by Badr et al (1997) that A. monosperma is tetraploid with 2n=36 and and A. judaica is diploid with 2n=16.…”
Section: Introductionmentioning
confidence: 99%